2016
DOI: 10.1177/1012690216640526
|View full text |Cite
|
Sign up to set email alerts
|

Finding the back of the net: Networks and migrant recruitment in Norwegian football

Abstract: The intention of this paper is to analyse the role that networks play in enabling the recruitment of a group of male migrant professional footballers employed by clubs based in Norway's top professional football league-the Tippeligaen. Based upon a series of semi-structured interviews conducted with migrants and recruiters, and synthesising concepts derived from the sociology of sport and the broader study of migration, the analysis identifies that the recruitment of migrant workers to Tippeligaen clubs reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Secondly, the recruitment activities of teams might be more geographically confined when, as in other labor markets, teams gather information about potential new players through informal networks maintained by their coaching and playing staff (Carter, 2011(Carter, , 2013Elliott and Gusterud, 2018). When these informal networks include players and coaches active in the same country, it follows that networks facilitate domestic mobility (Roderick, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the recruitment activities of teams might be more geographically confined when, as in other labor markets, teams gather information about potential new players through informal networks maintained by their coaching and playing staff (Carter, 2011(Carter, , 2013Elliott and Gusterud, 2018). When these informal networks include players and coaches active in the same country, it follows that networks facilitate domestic mobility (Roderick, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite the proliferation of such theoretical ideas, the recruitment activities of clubs and their role in global value added chains has so far mostly escaped researchers’ empirical attention (cf. Elliott and Gusterud, 2018; Velema, 2018). Without directly studying the recruitment activities of clubs, how teams shape the global value added chains and the flow of players around the world remains largely unknown.…”
mentioning
confidence: 99%
“…Given the fact that most athletes do not initially migrate to well‐established clubs and most sports clubs hold insufficient funds to secure profound knowledge about their new employees, informal social networks have been shown to be very influential in sports labor migration (Elliott and Maguire ). A number of studies have shown how male and female soccer players, as well as their coaches and club managers in various destinations around the world, use friends‐of‐friends networks to gather knowledge about conditions at destination clubs or about the player being recruited (Agergaard and Tiesler ; Elliott and Gusterud ). As has been described for women's soccer migration, friends‐of‐friends networks facilitate transnational exchange of knowledge between current and former coaches, and/or players, while governing bodies may also be involved in facilitating the migration of talented players (McCree ; Takahashi ).…”
Section: Being Transferred and Managing Initial Movesmentioning
confidence: 99%
“…Research into this area has grown significantly in the last three decades (Elliott & Gusterud, 2018;Lago-Peñas et al, 2019), especially those related to transnational migration on football and its most prominent European professional men leagues (Binder & Findlay, 2012;Elliott, 2013Elliott, , 2016Frick, 2009;. On the contrary, there is lack of studies and information specially on two dimensions: (a) intranational migration studies, which deserves attention from academic researchers because of its impact on social changes and cultural issues faced by migrants within the same country (Erel, 2010;McKinlay & McVittie, 2007;Roderick, 2013) and (b) research on migration related to other sports beyond football (Elliott & Maguire, 2008;Gavira et al, 2013), such as futsal (Moore et al, 2014;Tedesco, 2014) and its specific social scenarios, for example, in Brazil (Caregnato et al, 2015). Furthermore, little is still known about Brazilian sport labor context (Damo, 2014;de Souza & Martins, 2018;Marques & Marchi J unior, 2019) and its influence on intranational and transnational sport migration scenarios (Rubio, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the sociological approach is very suitable to understand the recruitment, moving, and actions of migrants (Elliott & Maguire, 2008;Guarnizo et al, 2019;O'Reilly, 2013), to describe the Brazilian futsal labor migration social context, as well as to understand players' intranational and transnational migration experiences, we based our study on sociological categories from Pierre Bourdieu's Reflexive Sociology and his Theory of Fields (Bourdieu, 1977(Bourdieu, , 1984(Bourdieu, , 1993(Bourdieu, , 1998Bourdieu & Wacquant, 1992), besides his contributions on reflections about migration (Bourdieu, 2004;Bourdieu & Wacquant, 2000).…”
Section: Introductionmentioning
confidence: 99%